2018
DOI: 10.1021/acsami.8b19768
|View full text |Cite
|
Sign up to set email alerts
|

Media Dependent Switching of Selectivity and Continuous near Infrared Turn-on Fluorescence Response through Cascade Interactions from Noncovalent to Covalent Binding for Detection of Serum Albumin in Living Cells

Abstract: Abnormal level of proteins is proved to be associated with diseases. Thus, protein sensing is helpful for clinical diagnosis and therapy. However, there is a great variety of protein species and relatively low concentration of each protein in complicated biological systems including other nonprotein biomolecules. Therefore, it remains challenging to develop an effective method for detecting protein with high selectivity and sensitivity. Herein, a new self-assembly method based on a robust dye SQSS of which two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To complement the above studies, a competition assay was performed with two known binders dansylamide (DNSA, for site I) and dansylproline (DP for site II) in Figure S11. 47 Because SQDC only partially enters the cavity of BSA, fewer binders are required in the competition experiment. After adding ONOO − , the SQ segment in the assembly can better enter the cavity due to the "destruction seek to survive" strategy, and increase the required competitive dose.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To complement the above studies, a competition assay was performed with two known binders dansylamide (DNSA, for site I) and dansylproline (DP for site II) in Figure S11. 47 Because SQDC only partially enters the cavity of BSA, fewer binders are required in the competition experiment. After adding ONOO − , the SQ segment in the assembly can better enter the cavity due to the "destruction seek to survive" strategy, and increase the required competitive dose.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results demonstrated that the reaction of SQDC@BSA with ONOO – afforded a large fluorescence change, thus amplifying the fluorescence change. To complement the above studies, a competition assay was performed with two known binders dansylamide (DNSA, for site I) and dansylproline (DP for site II) in Figure S11 . Because SQDC only partially enters the cavity of BSA, fewer binders are required in the competition experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The probe HJRA (2 μM) displays fluorescent-silent emission band at 598 nm (Figure S9) in ∼100% PBS buffer (pH 7.4, containing 0.2% DMSO) upon excitation at 539 nm. The nonemissive status may be due to the formation of loosely packed nanoaggregates resulting aggregation caused quenching (ACQ) effect and the presence of twisted intramolecular charge transfer process. Therefore, to establish the involvement of TICT process, change in photophysical (UV–vis absorption and fluorescence) behavior of probe was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, there are also few reports where some near-infrared (NIR) dyes bind with HSA to generate HSA–dye nanocomposites for applications in bioimaging, tumor therapeutic diagnosis, and potential drug delivery . However, Thayumanavan and colleagues have successfully employed the polymer–nanoparticle - disassembly strategy as a unique technique for the detection of both protein and enzyme. On the contrary, only a few examples exist where this disassembly technique was utilized successfully for small-molecule derived self-assembled nanoaggregated probes for the HSA and BSA detection. …”
Section: Introductionmentioning
confidence: 99%
“…Although many efficient fluorescent probes have been developed over the years for the specific detection of the albumin proteins (HSA/BSA) based on the probe-albumin chelation, many of these probes suffer from limitations, in terms of selectivity, high background signal, excitation/emission in the lower wavelength regions, and small Stokes shift, which essentially restricted their possible exploration in the in vivo biological models for advanced clinical investigations. On the other hand, NIR dyes such as Indocyanine Green (ICG), Cy5.5, and IRDye800CW have been used for detecting the location of SLNs in various tumors . However, these dyes involve a small Stokes shift (interference from excitation light) and the lack of any associated turn-on response mechanism.…”
Section: Resultsmentioning
confidence: 99%